Mathematical Modeling of Solar Power Generation Systems with Cross-Flow Cooling Pipes Based on Fuzzy Inference Systems - DA, Shazana; Tsalits, Askhaarina Aulia; Anshory, Izza; M, M. Syahrul; Jamaaluddin, Jamaaluddin; Darmansyah, Darmansyah (Faculty of Engineering, Universitas Tanjungpura, 2025)
The utilization of solar energy in Indonesia remains relatively low despite its high potential in terms of solar irradiation and geographical advantage. One of the main challenges in photovoltaic (PV) systems, especially in tropical climates, is the decline in performance caused by high operating temperatures. Unlike previous studies that primarily focused on passive cooling methods or basic active cooling without intelligent control, this research introduces a cross-mounted water pipe cooling system integrated with a Fuzzy Inference System (FIS) for dynamic water flow regulation, enabling optimal temperature control and dual-output (electrical and thermal) efficiency. Experimental testing on two 100 Wp monocrystalline solar panels—one with cooling and one without—under identical conditions revealed that the cooled panel achieved an average maximum power of 85.2 W, compared to 43.6 W for the non-cooled panel, with efficiency improvements of up to 7.4% over the observation period. A linear regression model was developed to predict PV performance under varying temperature conditions, demonstrating a slower decline in efficiency and more stable power output in the cooled system. The proposed hybrid PV/T configuration effectively dissipates heat while simultaneously recovering thermal energy, thus enhancing total energy utilization. These results highlight the system’s capability to mitigate thermal degradation, extend module lifespan, and promote sustainable renewable energy adoption in tropical regions. The integration of intelligent control with thermal management presents a scalable and energy-efficient approach for future photovoltaic applications.